The answer should be 14.
You just have to substitute x with the given number and finish the equation.
V = 4/3 * pi * r^3
V= 4/3 3.14 * 3^3
V = 4/3 *3.14 * 27
27 * 3.14 = 84.78
V = 4/3 * 84.78 = <span>113.04
V = </span><span>113.04
hope this helps</span>
B.
It can first be factored by splitting to:
(x + 1)(x^2 +4)
And (x^2 + 4) splits to x +/- 2i
Answer:
5.5 segments
Step-by-step explanation:
I am not sure if you meant 11/12 and 1/6 but here's how I solved it.
11/12 ÷ 1/6
11/12*6/1=
66/12 Simplify
5 6/12=5.5
Answer:
![f^{-1}(x)=2\pm\sqrt{x-3}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D2%5Cpm%5Csqrt%7Bx-3%7D)
Step-by-step explanation:
we have
![y=(x-2)^2+3](https://tex.z-dn.net/?f=y%3D%28x-2%29%5E2%2B3)
step 1
Exchange the variables (x for y and y for x)
so
![x=(y-2)^2+3](https://tex.z-dn.net/?f=x%3D%28y-2%29%5E2%2B3)
Isolate the variable y
step 2
![x=(y-2)^2+3](https://tex.z-dn.net/?f=x%3D%28y-2%29%5E2%2B3)
subtract 3 both sides
![(y-2)^2=x-3](https://tex.z-dn.net/?f=%28y-2%29%5E2%3Dx-3)
step 3
square root both sides
![y-2=\pm\sqrt{x-3}](https://tex.z-dn.net/?f=y-2%3D%5Cpm%5Csqrt%7Bx-3%7D)
step 4
Adds 2 both sides
![y=2\pm\sqrt{x-3}](https://tex.z-dn.net/?f=y%3D2%5Cpm%5Csqrt%7Bx-3%7D)
step 5
Let
![f^{-1}(x)=y](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3Dy)
![f^{-1}(x)=2\pm\sqrt{x-3}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%3D2%5Cpm%5Csqrt%7Bx-3%7D)